Resident perceptions of local offshore wind energy development: Modeling efforts to improve participatory processes. (February 2021) - Gonyo, Sarah Ball; Fleming, Chloe S.; Freitag, Amy; Goedeke, Theresa L.
Abstract: Federal agencies anticipate local opposition where wind energy projects are proposed. When opposition manifests as social action in later stages of project development, it can complicate projects. Therefore, it is important to understand what mediates local opposition and oppositional action so potential concerns can be addressed earlier. Results indicate that Carolina coast residents are supportive of local offshore wind energy development, despite little to no awareness of such developments and uncertainty about potential impacts. Awareness and certainty of impacts are the largest drivers of support level, followed by perceived impacts. Residents generally believe local offshore wind energy will improve local economies but damage the environment; however, perceived impacts vary by factor importance. About twice as many Carolina coast residents intend social action related to local offshore wind energy compared to those who have engaged in related past actions. Holding a strong position and engagement in past actions are the largest drivers of intended action. For those in strong opposition, increased place attachment increases the odds of intending action, suggesting place-protective action. These findings enhance understanding about relevant values and perceptions from a broader range of stakeholders, which decision-makers can use to improve public engagement and participatory processes. Highlights: Support for offshore wind energy, despite low awareness and low surety of impacts. Perceived benefits for local economies but perceived damages to the environment. Higher rates of intended action than past action related to offshore wind energy. Place-protective actions expected from attached residents. Proximity of household to the shoreline associated with intended action.